2022
DOI: 10.21037/qims-21-954
|View full text |Cite
|
Sign up to set email alerts
|

Left atrial booster-pump function as a predictive parameter for atrial fibrillation in patients with severely dilated left atrium

Abstract: Background: Left atrial (LA) dimension ≥50 mm had approximately four times the risk of developing atrial fibrillation (AF). The aim of this study was to investigate whether the application of clinical and echocardiographic parameters could differentiate between the patients having severely dilated left atrium with and without AF.Methods: This retrospective cross-sectional study enrolled consecutive patients with LA dimension ≥50 mm and divided them into three groups: no AF (no-AF), paroxysmal AF (PAF) and non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
0
2
0
2
Order By: Relevance
“…Tuy nhiên, nếu rung nhĩ diễn ra quá lâu sẽ dẫn đến những thay đổi mang tính cố định ở cấu trúc cơ của nhĩ trái như xơ hoá, sợi hoá và lâu dần sẽ dẫn đến giãn nhĩ như một cơ chế đáp ứng bù trù. Khi có rung nhĩ thì chức năng trữ máu và dẫn máu vẫn còn duy trì, tuy nhiên chức năng co bóp của nhĩ trái đã bị mất đi [7]. Khi có hồi phục lại nhịp xoang thì chức năng này có thể quay trở lại và có thể suy giảm.…”
Section: Bàn Luậnunclassified
“…Tuy nhiên, nếu rung nhĩ diễn ra quá lâu sẽ dẫn đến những thay đổi mang tính cố định ở cấu trúc cơ của nhĩ trái như xơ hoá, sợi hoá và lâu dần sẽ dẫn đến giãn nhĩ như một cơ chế đáp ứng bù trù. Khi có rung nhĩ thì chức năng trữ máu và dẫn máu vẫn còn duy trì, tuy nhiên chức năng co bóp của nhĩ trái đã bị mất đi [7]. Khi có hồi phục lại nhịp xoang thì chức năng này có thể quay trở lại và có thể suy giảm.…”
Section: Bàn Luậnunclassified
“…Достаточно изучено, что определенный сегмент миокарда ЛП имеет свои нормальные значения деформации и скорости деформации. Задняя стенка ЛП подвержена наименьшей деформации, вероятнее всего, это связано с впадением легочных вен и их плотной фиксацией [30], нижняя стен-Рис. 4.…”
Section: трансторакальнаяunclassified
“…This result suggests that LA dysfunction plays a more pivotal role than LA enlargement in the development of AF. Recently, our group demonstrated that LAEF, , LASr, pLASRr, and pLASRct were associated with the occurrence of AF, and multivariate regression analysis revealed that pLASRct was the only independent factor associated with the absence of AF in those with LAD 50 mm [ 112 ]. Atrial booster pump function represents the inherent contractility of the LA myocardium.…”
Section: Review Of Parametersmentioning
confidence: 99%